Ground-based detection of an extended helium atmosphere in the Saturn-mass exoplanet WASP-69b - Nortmann, Lisa; Yan, Fei; Henning, Thomas; Quirrenbach, Andreas (Arxiv, 2018)
Hot gas giant exoplanets can lose part of their atmosphere due to strong stellar irradiation, affecting their physical and chemical evolution. Studies of atmospheric escape from exoplanets have mostly relied on space-based observations of the hydrogen Lyman-α line in the far ultraviolet which is strongly affected by interstellar absorption. Using ground-based high-resolution spectroscopy we detect excess absorption in the helium triplet at 1083 nm during the transit of the Saturn-mass exoplanet WASP-69b, at a signal-to-noise ratio of 18. We measure line blue shifts of several km/s and post transit absorption, which we interpret as the escape of part of the atmosphere trailing behind the planet in comet-like form. [Additional notes by authors: Furthermore, we provide upper limits for helium signals in the atmospheres of the exoplanets HD 209458b, KELT-9b, and GJ 436b. We investigate the host stars of all planets with detected helium signals and those of the three planets we derive upper limits for. In each case we calculate the X-ray and extreme ultraviolet flux received by these planets. We find that helium is detected in the atmospheres of planets (orbiting the more active stars and) receiving the larger amount of irradiation from their host stars.]